Penerapan Prinsip ISO 9001:2000 di Lembaga Pendidikan - Mulyono, Mulyono (UIN Maulana Malik Ibrahim Malang, 2006)
The fast development of science, technology and rapid change in this life has recently been an inevitable phenomenon. Education institution as an open social institution regarded as agent of change is demanded to respond this change. The decree No. 20, 2003 about National Education System Section 50 article 3 conceded that the central and local government should conduct at least one education unit to all education levels projected to meet international standard. One of the efforts to reach education with either national or international standard is by the implementation of quality management ISO. One of the characteristics of education institution with international standard is the implementation of management ISO 9001:2000. This article will deal with the implementation of management ISO 9001:2000 in education institution. The implementation of this standard requires quality control unit that plays the role as internal audit institution. Therefore it can foster the realization of Islamic education institution that meets international standard. Perkembangan sains, teknologi dan perubahan cepat dalam kehidupan ini baru-baru ini menjadi fenomena yang tak terelakkan. Lembaga pendidikan sebagai lembaga sosial terbuka yang dianggap sebagai agen perubahan dituntut untuk merespon perubahan ini. Keputusan No. 20, 2003 tentang Sistem Pendidikan Nasional Bagian 50 pasal 3 mengakui bahwa pemerintah pusat dan daerah harus melakukan setidaknya satu unit pendidikan ke semua tingkat pendidikan yang diproyeksikan untuk memenuhi standar internasional. Salah satu upaya untuk mencapai pendidikan dengan standar nasional maupun internasional adalah dengan penerapan ISO manajemen mutu. Salah satu ciri lembaga pendidikan dengan standar internasional adalah penerapan manajemen ISO 9001: 2000. Artikel ini membahas penerapan manajemen ISO 9001: 2000 di lembaga pendidikan. Implementasi standar ini membutuhkan unit kontrol kualitas yang berperan sebagai lembaga audit internal. Oleh karena itu dapat menumbuhkan kesadaran lembaga pendidikan Islam yang memenuhi standar internasional.